Application of AI Face Recognition Technology in Swipe Card Attendance Systems for Hospitals - Wang, Te-Kwei; Lin, Yu-Hsun; Li, Kai-Ping (Proceedings of Engineering and Technology Innovation, 2022)
Traditional swipe card attendance systems for hospitals cannot effectively protect employees’ personal information and ensure that the employees are swiping their own cards. To solve the problem, the present study proposes a novel hospital swipe card attendance system using an artificial intelligence (AI) face modeling system with an open-source face database. The proposed system employs a multi-task cascaded convolutional network (MTCNN) algorithm and FaceNet to improve the performance of face recognition. The system can compare the face of the one who swipes a card with the faces of cardholders in the database, thereby preventing the one from clocking in on behalf of others. The results show that the application of AI technology in the hospital swipe card attendance system can realize the promise of protecting employees’ personal information and verifying employees’ identities.